The role of the teaching practice in undergraduate education – A British perspective. Issue 2 (1st May 2018) - Houlston, Patricia
Abstract : This article describes and reflects on the role of the teaching practice in undergraduate education on the basis of the author's experience in the United Kingdom. Recognizing that China is addressing the huge task of developing a general practice workforce in an unprecedented short time, I hope that sharing these ideas will be helpful. General practitioners are well able to teach the basics of medicine. However, their real strengths come when they are focusing on key consulting skills needed for general practice, developing reflective lifelong learners, and cultivating good attitudes. The practice is also able to demonstrate preventive medicine, chronic disease management, and multidisciplinary care. By providing exposure to general practice at this early stage in a medical career, the teaching practice will hopefully inspire and attract the general practice workforce of the future.